Determinants of Disagreement with Female Genital Mutilation Among Mothers - Keles E; Eker HH; Bektemur G; Hilowle IA; Kassim MM; Hassan-Kadle MA; Adali A; Karaketir Ş (Dove Medical Press, 2022)
Esra Keles,1 Hasan Huseyin Eker,2 Guven Bektemur,3 Ifrah Adan Hilowle,4 Mohamed Mukhtar Kassim,5 Mohamed Abdulkadir Hassan-Kadle,6,7 Ali Adali,5 Şeyma Karaketir8 1Department of Gynecologic Oncology, University of Health Sciences Turkey, Kartal Lütfi Kırdar City Hospital, Istanbul, Turkey; 2Department of Public Health, University of Health Sciences Turkey, Mogadishu Somalia-Turkey Recep Tayyip Erdoğan Training and Research Hospital, Mogadishu, Somalia; 3Department of Public Health, University of Health Sciences Turkey, Faculty of Hamidiye Medicine, Istanbul, Turkey; 4Department of Education, University of Health Sciences Turkey, Mogadishu Somalia-Turkey Recep Tayyip Erdoğan Training and Research Hospital, Mogadishu, Somalia; 5Department of Pediatrics, University of Health Sciences Turkey, Mogadishu Somalia-Turkey Recep Tayyip Erdoğan Training and Research Hospital, Mogadishu, Somalia; 6College of Medicine and Health Science, Abrar University, Mogadishu, Somalia; 7CenterFor Digestive & Liver Diseases, SomGastro Clinic, Mogadishu, Somalia; 8Department of Public Health, Istanbul University, Occupational Health Training Programme, Istanbul School of Medicine, Istanbul, TurkeyCorrespondence: Mohamed Abdulkadir Hassan-Kadle, College of Medicine and Health Science, Abrar University, Hodan District, Benadir Region, Mogadishu, Somalia, Tel +252 68 5910409, Email dr.kadle@abrar.edu.soAim: Female genital mutilation (FGM) is widely practiced in Somalia. Limited data are available on the attitude of the Somalia community regarding FGM. The present study aimed to explore the attitude of mothers toward the practice of FGM.Methods: A cross-sectional study was conducted from March to July 2021 among mothers attending outpatient clinics at a tertiary referral hospital in Mogadishu, Somalia.Results: A total of 247 participants were included, 65.2% of whom believed this practice should be continued. The most cited reason reported regarding FGM was a requirement for religion (90.7%). About 73.9% of mothers stated that the most cited reason reported regarding the abandonment of FGM was health complications. About 59.8% of the study participants thought that FGM could be stopped through education. The results revealed that women who graduated from primary school (OR: 2.21; 95% CI: 1.090- 4.51), who had no social media account (OR: 2.305; 95% CI: 1.147- 4.633), and women who were circumcised by a traditional birth attendant (OR: 4.55; 95% CI: 1.57- 13.22) were more likely to think that FGM should be continued compare with their counterparts.Conclusions: We found that mothers who were less educated, had no social account and those circumcised by a traditional birth attendant had more positive attitudes toward FGM.Keywords: female genital mutilation, female genital cutting, education, Somalia